2002
DOI: 10.1016/s1044-0305(02)00423-3
|View full text |Cite
|
Sign up to set email alerts
|

A study of fast and metastable dissociations of adenine-thymine binary-base oligonucleotides by using positive-ion MALDI-TOF mass spectrometry

Abstract: In the present study, fast and metastable dissociations of a number of adenine-thymine binary-base oligonucleotides under the conditions of UV matrix-assisted laser desorption/ ionization mass spectrometry were investigated. 2-Aminobenzoic acid/ammonium fluoride (ABA/NH 4 F) matrix system was used. The spectra obtained under metastable and fast dissociation conditions exhibit distinctive dissociation products. From the post-source-decay analysis, all oligonucleotides underwent predominantly metastable dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A base loss is considered to be a critical step of this "thermal" fragmentation pathway [75,76]. Alternatively, a pathway of electronic energy transfer was also proposed to occur in positive ion mode with 2-aminobenzoic acid and leads to the formation of supplementary ions (d-, b-, and y-ions) [77]. Concerning applications of ISD in the nucleic acids field, ISD was successfully applied by Wang et al to sequence covalently modified (phosphorothioate instead of phosphodiester bonds) oligonucleotides [78] but failed to allow locating covalent rhodium adducts on DNA [79].…”
Section: Maldi-isd Of Oligonucleotidesmentioning
confidence: 99%
“…A base loss is considered to be a critical step of this "thermal" fragmentation pathway [75,76]. Alternatively, a pathway of electronic energy transfer was also proposed to occur in positive ion mode with 2-aminobenzoic acid and leads to the formation of supplementary ions (d-, b-, and y-ions) [77]. Concerning applications of ISD in the nucleic acids field, ISD was successfully applied by Wang et al to sequence covalently modified (phosphorothioate instead of phosphodiester bonds) oligonucleotides [78] but failed to allow locating covalent rhodium adducts on DNA [79].…”
Section: Maldi-isd Of Oligonucleotidesmentioning
confidence: 99%
“…The ability to handle large DNA and RNA fragments should facilitate high-throughput screening applications for genotyping and clinical diagnosis. It has also been shown that the PSD technique is effective to investigate oligonucleotide fragmentation processes (Chan, Fung, & Li, 2002).…”
Section: A Proteins and Peptidesmentioning
confidence: 99%
“…There has been substantial effort to understand the fragmentation mechanism behind the prompt and metastable decay of oligonucleotides in MALDI 4–7, 9, 23–32. Much of this work was reviewed by Wan and Gross in 2001 and by Wu and McLuckey in 2004 6, 32.…”
mentioning
confidence: 99%